R. Macperson. Rome in Involution. Cassiodorus Variae in their litheracy and historical setting. Pozman, Uniwersytet im. Adama Mickiewicza Poznaniu. Pozman. 1989. 367 págs. - MORENO, Francisco J. (Gerión. Revista de Historia Antigua, 1990)
Sin resumen